Silica matrices doped with red laser dyes - Pritula, I.M.; Bezkrovnaya, O.N.; Puzikov, V.M.; Maslov, V.V.; Plaksiy, A.G.; Lopin, A.V.; Gurkalenko, Yu.A. (Functional Materials, 2012)
Sol-gel SiO₂ matrices activated with laser dyes for the red spectral region DCM, LK678 and benzopyran derivatives LD1 and LD2 were synthesized. Pyridine was used to prevent bleaching of the dyes during the synthesis of the matrices. Studied were the spectral and luminescent characteristics of the laser dyes in SiO₂ matrices. Laser pumping of DCM and LK678 made it possible to obtain stimulated emission. The laser efficiency of LK678 dye in the matrix was 1.5 times as high as that of rhodamine 6G. The absence of lasing radiation of the benzopyran derivatives LD1 and LD2 in the synthesized matrices was explained.